MANAJEMEN KEPALA MADRASAH DALAM PENGEMBANGAN MADRASAH EFEKTIF DI MADRASAH TSANAWIYAH PP MU’ALLIMIN MUHAMMADIYAH SAWAH DANGKA AGAM - Yuni Susanti (IAIN Batusangkar, 2019)
The purpose of this study was to determine planning, organizing, implementing and monitoring activities carried out by principal of MTs PP Mu'allimin Muhammadiyah Sawah Dangka in the development of effective madrasah. The design of research was descriptive qualitative. Research informants were 9 people. Data collection tools are researchers as key instruments and supporting instruments are interview guidelines, observation guidelines, field notes, and cellphones. Data collection techniques are observation, indepth interviews and documentation studies. Data analysis techniques in this study using a model conducted by Matthew B. Miles and A. Michael Huberman. The technique of testing the validity of data using data triangulation and methods. The results showed that the principal of MTs PP Mua'limin Muhammadiyah Sawah Dangka was able to carry out management functions ranging from planning, organizing, implementing and supervising the effective madrasah indicators